Impact of patatin‐like phospholipase domain containing 3 rs738409 G/G genotype on hepatic decompensation and mortality in patients with portal hypertension. Issue 4 (29th June 2018) - Mandorfer, M.; Scheiner, B.; Stättermayer, A. F.; Schwabl, P.; Paternostro, R.; Bauer, D.; Schaefer, B.; Zoller, H.; Peck‐Radosavljevic, M.; Trauner, M.; Reiberger, T.; Ferenci, P.; et al.
Summary: Background: The rs738409 C>G p.I148M variant in the patatin‐like phospholipase domain containing 3 ( PNPLA3 )‐gene promotes triglyceride accumulation in hepatocytes and hepatic stellate cell activation and has previously been linked to hepatic steatosis/liver fibrosis. Aim: To investigate its impact on hepatic decompensation and (liver‐related) mortality in patients who had already developed portal hypertension. Moreover, we assessed its link with hepatic steatosis as evaluated by controlled attenuation parameter. Methods: We performed a retrospective analysis in prospectively characterised patients with viral hepatitis/fatty liver disease‐induced portal hypertension (hepatic venous pressure gradient [HVPG] ≥ 6 mm Hg) diagnosed at the Medical University of Vienna who underwent HVPG measurement (until 2013; n = 372; longitudinal study) or simultaneous HVPG and controlled attenuation parameter measurement (2014‐2017; n = 153; cross‐sectional study). Results: While survival was similar between PNPLA3‐ C/C and ‐C/G patients, we observed substantially increased mortality in PNPLA3‐G/G patients. PNPLA3‐G/G had no impact on mortality in the subgroup of patients with viral hepatitis; however, we observed a strong independent association between PNPLA3‐G/G and hepatic decompensation (adjusted subdistribution hazard ratio [aSHR]: 2.1, 95% confidence interval [95% CI]: 1.1‐4; P  =   0.024) as well as mortality (overall: aSHR: 2.2, 95% CI: 1.22‐3.98; P  =   0.009; liver‐related: aSHR: 2.2, 95% CI: 1.08‐4.46; P  =   0.029) in patients with fatty liver disease. Interestingly, even in the subgroup of patients who had already progressed to clinically significant portal hypertension (HVPG ≥ 10 mm Hg), PNPLA3‐G/G substantially increased mortality (aSHR: 2.33, 95% CI: 1.27‐4.29; P  =   0.006). PNPLA3 ‐genotype had no influence on controlled attenuation parameter or the prevalence of values ≥248 dB/m. Conclusion: PNPLA3‐G/G ‐genotype seems to double the risks of hepatic decompensation and (liver‐related) mortality in patients with portal hypertension due to fatty liver disease. Further studies are warranted to investigate potential underlying pathophysiological mechanisms unrelated to hepatic steatosis.